Filling the Knowledge-to-Action Gap with Open Access Pedagogy: An Alternative Assignment Model - Jennifer L. Briere; Ishita B. Zaman; Sophia Haotong Wang (Open Praxis, 2022)
Knowledge translation (KT) is key to the scientific process, yet academic work produced often does not reach the public. In this article a unique undergraduate KT term assignment is presented where students summarize a large body of research into an artifact for public use. This assignment model may increase student engagement and learning outcomes while filling the knowledge-to-action translation gap. The option dovetails students’ and employers’ need for demonstrative performance prior to hiring, the academic push for publicly and freely available scientific knowledge (e.g., open access), and challenges involved with engagement with advanced material in both in-person and remote environments. The assignment is presented in the context of benefitting effective KT and enhancing open access to information; it is then analyzed using the American Psychological Association’s (APA) goals for undergraduates alongside Bloom’s Taxonomy of Learning. Various APA goals accomplished through the assignment, benefits, limitations, and future directions are highlighted.